Competing Effects of Doping and Trap Formation in Polymer Semiconductors During Plasma Treatment - Yu, Hongquan; Tang, Zhenyuan; Tu, Min; Wu, Yangjiang; Zhang, Kaihuan (IEEE electron device letters, 2024)
Plasma treatment has been extensively employed for doping or etching organic semiconductors. Both doping and etching effects occur simultaneously during the plasma treatment. Polymer semiconductors, which contain both crystalline and amorphous phases, exhibit inherent selective etching characteristics. However, the combined effects of doping and selective etching on the electrical properties of polymer semiconductors have not been thoroughly investigated. In this study, we examine the influence of plasma treatment on the surface morphology and electrical properties of organic field-effect transistors utilizing the polymer semiconductor DPP-DTT. A competitive effect between doping and trap formation is observed during plasma treatment, resulting in controllable bidirectional shifts in threshold voltage with acceptable mobility degradation. Under optimal plasma treatment conditions, a 3.45-fold increase in the current response and improved recovery performance were observed in NO2 gas sensing applications, attributed to the formation of trap and the pore structure from selective etching. These results highlight the significant potential of plasma treatment for optimizing polymer-based organic transistors.